Security of Mobile Radiological Sources: Overview of Industry Applied Technologies - Ann M Archer; Ashleigh Wickham (International Journal of Nuclear Security, 2024)
Small radiological sources used in industrial settings recurrently require transit between job sites. Securing these sources, while stationary, can be addressed with standard security approaches and equipment. Transport of these sources increases the risk and complexity of managing and maintaining control of these sources. Implementing methodologies to securely monitor and locate sources improves response and resolution of anomalous events during transit. The Mobile Source Transit Security (MSTS) system was developed to improve security and provide situational awareness of these mobile sources throughout their job cycle. The MSTS development effort focused on creating a set of systems that could be successfully implemented in industrial radiography and well-logging applications. The MSTS team worked to address source presence and location through use and storage. The MSTS system monitors radiological sources as they move from the base of operations to the job site and back. The system provides near-real-time monitoring of the mobile source location and status and early notification of source loss or theft by transmitting operational status and alerting anomalous conditions over telematic links worldwide. The MSTS system can trigger an armed response or initiation of search and recovery operations and will automatically alert management and responsible staff if a radioactive source is lost or stolen whether it is on-site, in transport, or in storage.
Keywords: Mobile Source Transit Security; mobile radiological sources; nuclear security; well-logging; industrial radiography